Mitochondrial calcium uniporter blocker effectively prevents brain mitochondrial dysfunction caused by iron overload - Sripetchwandee J. (2014)
Aims Although iron overload induces oxidative stress and brain mitochondrial dysfunction, and is associated with neurodegenerative diseases, brain mitochondrial iron uptake has not been investigated. We determined the role of mitochondrial calcium uniporter (MCU) in brain mitochondria as a major route for iron entry. We hypothesized that iron overload causes brain mitochondrial dysfunction, and that the MCU blocker prevents iron entry into mitochondria, thus attenuating mitochondrial dysfunction. Main methods Isolated brain mitochondria from male Wistar rats were used. Iron (Fe2 + and Fe3 +) at 0-286 μM were applied onto mitochondria at various incubation times (5-30 min), and the mitochondrial function was determined. Effects of MCU blocker (Ru-360) and iron chelator were studied. Key findings Both Fe2 + and Fe3 + entered brain mitochondria and caused mitochondrial swelling in a dose- and time-dependent manner, and caused mitochondrial depolarization and increased ROS production. However, Fe 2 + caused more severe mitochondrial dysfunction than Fe 3 +. Although all drugs attenuated mitochondrial dysfunction caused by iron overload, only an MCU blocker could completely prevent ROS production and mitochondrial depolarization. Significance Our findings indicated that iron overload caused brain mitochondrial dysfunction, and that an MCU blocker effectively prevented this impairment, suggesting that MCU could be the major portal for brain mitochondrial iron uptake. © 2013 Elsevier Inc.